A new approach to predictive of fragmentation in the Blast Of Rocks - Rojas Linares, Edito Luis (2018)
The objective of this research work is to provide a new predictive approach to fragmentation in the rock blasting processes, developed based on the Kuz-Ram model, Multivariate Analysis techniques (MVA) and Artificial Neural Network techniques (ANN).The objective of the new approach predictive approach to (X50), fragmentation is based on the fact that this research, would provide us with an optimization in the metallurgical mining operations, because delivering an optimal fragmentation requerid for the grinding processes, it could minimize their times and maximize their productivity.